Biomarkers of Exposure to Zearalenone in In Vivo and In Vitro Studies - Paula Llorens; Marta Herrera; Ana Juan-García; Juan José Payá; Juan Carlos Moltó; Agustín Ariño; Cristina Juan (Toxins, 2022)
The measurement of human exposure to mycotoxins is necessary for its association with adverse health effects. This exposure is usually estimated from contamination levels of foodstuffs, which are the primary source of toxin exposure, and data on food consumption patterns. However, variations in contamination level, intestinal absorption, toxin distribution, and excretion lead to individual variations in toxin exposure that can be more readily measured with a biomarker. This review deals with the latest literature information about ZEN biomarkers in humans, animals, and cell line cultures. Their presence in urine, biomarkers that have effects in the kidney, liver, reproductive system and blood and biomarkers of cell response have been reported. It has highlighted the importance of determining α-zearalenol and β-zearalenol biomarkers to estimate the probable dietary intake (PDI) of a specific population or to characterize the severity of exposure to ZEN in animals or cell lines. α-ZEL and β-ZEL are cytotoxic by inhibiting cell proliferation, total protein and DNA syntheses, in this sense, an induction of expression proteins Hsp27 and Hsp70 was observed, and an increase in gene expression (TLR4, NF-kBp65, TNF-α, IL-1β, IL-6, IL-8, MGMT, α-GST, Hsp70, Nrf2, L-Fabp, HO-1, MAPK8), the determination of which indicates an oxidative stress effect. The integrity of the cell or tissue membrane is assessed by lactate dehydrogenase (LDH), which increase at exposure of ZEN (84.2 µM), and the proportions of some fatty acids of the renal tissue membrane were increased at treatments with ZEN. This review allows starting future studies of animal and population exposure in parallel with those of health effects works.